2010
DOI: 10.1007/s10532-010-9336-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of the major color containing compounds in distillery wastewater by an aerobic bacterial culture and characterization of their metabolites

Abstract: This study deals the biodegradation of the major color containing compounds extracted from distillery wastewater (DWW) by an aerobic bacterial consortium comprising Bacillus licheniformis (DQ79010), Bacillus sp. (DQ779011) and Alcaligenes sp. (DQ779012) and characterization of metabolic products. The degradation of color containing compounds by bacteria was studied by using the different carbon and nitrogen sources at different environmental conditions. Results revealed that the bacterial consortium was effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…(DQ779011), and Alcaligenes sp. (DQ779012) used for decolourization by Bharagava and Chandra [28], the use of the additive of organic nitrogen source (peptone) in an amount greater than 1 g dm -3 , as in our studies after increasing the dose (more than 2.24 g dm -3 ), contributed to a reduction in the degree of removal of colour. Yadav and Chandra [20] also reported that doses of more than 1 g dm -3 of organic nitrogen source showed an inhibitory effect on the decolourization process.…”
Section: Resultssupporting
confidence: 55%
“…(DQ779011), and Alcaligenes sp. (DQ779012) used for decolourization by Bharagava and Chandra [28], the use of the additive of organic nitrogen source (peptone) in an amount greater than 1 g dm -3 , as in our studies after increasing the dose (more than 2.24 g dm -3 ), contributed to a reduction in the degree of removal of colour. Yadav and Chandra [20] also reported that doses of more than 1 g dm -3 of organic nitrogen source showed an inhibitory effect on the decolourization process.…”
Section: Resultssupporting
confidence: 55%
“…Melanoidins are complex, dark coloured, amino-carbonyl polymeric compounds with high molecular weight, formed by non-enzymatic browning Maillard reaction (MR) during several industrial processes (Hayase 2000 ; Echavarría et al 2014 ; Bharagava and Chandra 2010 ). The major sources of melanoidins in environment are sugarcane-molasses based distilleries and fermentation industries all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been tried to remove melanoidin color and recalcitrant COD. Biological processes employing bacteria [9], fungi [10], and enzyme [11] have been tried before to treat melanoidin-rich wastewater. Though biological processes are generally less costly than chemical or physical treatment methods, none of the reported methods can effectively remove the contaminants in melanoidin-rich wastewaters.…”
Section: Introductionmentioning
confidence: 99%